Simultaneous measurements of unstable and stable Alfvén eigenmodes in JET. (1st November 2022) - Tinguely, R.A.; Gonzalez-Martin, J.; Puglia, P.G.; Fil, N.; Dowson, S.; Porkolab, M.; Kumar, I.; Podestà, M.; Baruzzo, M.; Fasoli, A.; Kazakov, Ye.O.; Nave, M.F.F.; et al.
Abstract: In this paper, we report the novel experimental observation of both unstable and stable toroidicity-induced Alfvén eigenmodes (TAEs) measured simultaneously in a JET tokamak plasma. The three-ion-heating scheme (D-DNBI- 3 He) is employed to accelerate deuterons to MeV energies, thereby destabilizing TAEs with toroidal mode numbers n = 3–5, each decreasing in mode amplitude. At the same time, the Alfvén eigenmode active diagnostic resonantly excites a stable n = 6 TAE with total normalized damping rate − γ / ω 0 ≈ 1%–4%. Hybrid kinetic-MHD modeling with codes NOVA-K and MEGA both find eigenmodes with similar frequencies, mode structures, and radial locations as in experiment. NOVA-K demonstrates good agreement with the n = 3, 4, and 6 TAEs, matching the damping rate of the n = 6 mode within uncertainties and identifying radiative damping as the dominant contribution. Improved agreement is found with MEGA for all modes: the unstable n = 3–5 and stable n = 2, 6 modes, with the latter two stabilized by higher intrinsic damping and lower fast ion drive, respectively. While some discrepancies remain to be resolved, this unique validation effort gives us confidence in TAE stability predictions for future fusion devices.